STRUKTUR PENDANAAN DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI - Asmoro, Sugeng Riyadi; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of funding structure to the firm value with the managerial ownership as the moderating at chemical companies which are listed in Indonesia Stock Exchange during the 2011-2013 periods. The samples of the research have been selected by using purposive sampling 10 chemical companies (30 firm years) which meet the criteria have been selected as samples. The regression equation in this research is the Moderated Regression Analysis (MRA) which is applied to test whether the moderating variable can strengthen or weaken the correlation among the independent variables to the dependent variable. The multiple regressions which is done by using SPSS 16 version program, is used as the analysis technique. Based on the result of multiple regressions analysis with the significant influence of 5% therefore this research describes that: (1) H1 is the funding structure which has influence to the firm value with its significance level is 0.054 cannot be accepted since the value of t count is -2.021 which leads to the negative direction; (2) H2 is the managerial ownership which has influence to the firm value with its significance level is 0.007 cannot be accepted since the value of t count is -2.901 which leads to the negative direction; (3) H3 is the managerial ownership positively moderates the correlation of funding structure to the firm value with its significance level is 0.025 and the t count is 2.371. Therefore, the managerial ownership can positively moderate the correlation between funding structure and firm value.Keywords: funding structure, managerial ownership, and firm value.